Ośrodki Pomocy Społecznej w systemie polityki społecznej państwa - Brenk, Mikołaj (My University, 2015)
The following article is about the first Polish bill regulating the matter of social care - the Bill from 16th August 1923 on Social Care. The task of the bill was to standardize the rules concerning giving help to the needing ones on the area of Polish lands which belonged to the three occupant countries. The Bill was based on the Prussian law of social service, meaning the Bill of Residential Relief from 1870, according to which it was the lowest level of government, meaning the municipality, that was responsible for the tasks connected with social care.
Social Welfare Centres (OPS) in the national social policy system
Keywords: ośrodek pomocy społecznej; MOPS; pomoc społeczna